2008
DOI: 10.1002/ejic.200700959
|View full text |Cite
|
Sign up to set email alerts
|

Application of New Organic Fuels in the Direct MgAl2O4 Combustion Synthesis

Abstract: The paper presents a new version of MgAl 2 O 4 solution-combustion synthesis, based on the individual reactivity of Mg(NO 3 ) 2 and Al(NO 3 ) 3 with respect to various fuels. Beside the traditionally used fuels (urea, glycine, β-alanine), new organic reducing agents [monoethanolamine, triethanolamine, tris(hydroxymethyl)aminomethane and triethylenetetramine] have also been used. The study of the individual reactivities of Mg(NO 3 ) 2 and Al(NO 3 ) 3 with respect to each of the previously mentioned fuels sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 26 publications
1
5
0
2
Order By: Relevance
“…At higher temperatures, the sample still lost mass in two weak steps up to 1100°C. The total mass loss was about 85%, in accordance with previous works . The mass loss behavior was found to be independent of the spinel stoichiometric ratio or lithium addition.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…At higher temperatures, the sample still lost mass in two weak steps up to 1100°C. The total mass loss was about 85%, in accordance with previous works . The mass loss behavior was found to be independent of the spinel stoichiometric ratio or lithium addition.…”
Section: Resultssupporting
confidence: 91%
“…The total mass loss was about 85%, in accordance with previous works. [23][24][25][26] The mass loss behavior was found to be independent of the spinel stoichiometric ratio or lithium addition.…”
Section: Resultsmentioning
confidence: 93%
“…In order to counteract the disadvantage of using redox inert SiO 2 , a fuel mixture of urea and monoethanolamine (molar ratio 13:2) was used in samples 1 and 2, which is supposed to ensure the most exothermic combustion reaction. Our previous results have shown that starting from Mg(NO 3 ) 2 , Al(NO 3 ) 3 (molar ratio 1:2) and a mixture of urea and monoethanolamine (molar ratio 13:2) leads to the formation of pure and well crystallized MgAl 2 O 4 directly from the reaction of combustion [28].…”
Section: Resultsmentioning
confidence: 99%
“…If urea is a better fuel for aluminium nitrate than glycine [15], in the case of yttrium nitrate, the situation is exactly the opposite: glycine is more suitable than urea [16]. A better fuel triggers a more exothermal combustion reaction.…”
Section: Methodsmentioning
confidence: 94%